Autos eletrônicos na Justiça Federal da 2ª Região: a contribuição do processo eletrônico na redução do tempo de tramitação dos processos - Olivieri, Rosângela do Carmo (2010)
This study aimed to examine the contribution of the electronic process in reducing the average length of the proceedings. To achieve this goal, we carried out descriptive documentary, with field data collected in June 2009, in fourteen Special Federal Courts and three Courts of Appeal in the 2nd Region, totaling 1444 cases (physical and electronic) that reached their conclusion that month. The main results indicate that during the period observed, the electronic process is faster than the physical process, reaching on average 70% reduction in length of the proceedings. It was also found that this reduction is variable in time among distinct stages of the processo Based on these results and directions of the doctrine, it is proposed to create an indicator of average time of proceedings, which indicates the current occurrence of each stage selected, as well as past behavior, since both make reference to analysis and study of situations and future decision-making associated with the speed of adjudication, without loss of quality of the results already obtained. The electronic process is one of the tools used to address delays in the judicial branch and can help increase the Index of Confidence in Justice in Brazil, strengthening the judiciary and enhancing access to justice. In the end, we present conclusions and suggestions which are intended to accelerate and expand access to justice.